2020
DOI: 10.3390/cells9071631
|View full text |Cite
|
Sign up to set email alerts
|

Basophils from Cancer Patients Respond to Immune Stimuli and Predict Clinical Outcome

Abstract: Basophils are involved in manifestations of hypersensitivity, however, the current understanding of their propensity for activation and their prognostic value in cancer patients remains unclear. As in healthy and atopic individuals, basophil populations were identified in blood from ovarian cancer patients (n = 53) with diverse tumor histologies and treatment histories. Ex vivo basophil activation was measured by CD63 expression using the basophil activation test (BAT). Irrespective of prior treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 94 publications
(133 reference statements)
4
38
0
Order By: Relevance
“…A direct anti-tumor effect of eosinophils in a melanoma mouse model was shown to be dependent on the presence of IL-33 in the TME [ 277 ]. High relative circulating basophils and activated infiltrated basophils were positively associated with improved outcome in melanoma or ovarian cancer patients and, according to several data, basopenia was associated with a poor prognosis in colorectal cancer [ 278 , 279 , 280 ].…”
Section: Eosinophils and Basophilsmentioning
confidence: 99%
“…A direct anti-tumor effect of eosinophils in a melanoma mouse model was shown to be dependent on the presence of IL-33 in the TME [ 277 ]. High relative circulating basophils and activated infiltrated basophils were positively associated with improved outcome in melanoma or ovarian cancer patients and, according to several data, basopenia was associated with a poor prognosis in colorectal cancer [ 278 , 279 , 280 ].…”
Section: Eosinophils and Basophilsmentioning
confidence: 99%
“…In a recent study, Bax and co-workers examined the role of basophils in ovarian cancer patients (204). They found that higher percentage of circulating basophils from ovarian cancer patients was positively associated with improved overall survival.…”
Section: Basophils and Ovarian Cancermentioning
confidence: 99%
“…It has long been known that human ( 127 131 ) and mouse ( 62 , 73 , 124 126 ) basophils have a propensity to migrate from peripheral blood into sites of inflammation. Moreover, basophils were identified in human lung ( 50 ), gastric ( 127 , 128 ), pancreatic ( 11 , 91 ) and ovarian cancer ( 204 ). It was recently shown, at least in mice, that basophils are present in all phases of lung development ( 44 ), and display a divergent phenotype from peripheral blood.…”
Section: Conclusion and Outstanding Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients with cancer may develop antitumour IgE: greater numbers of IgE-expressing cells have been observed in head and neck tumours compared to normal mucosa [ 6 ] and an IgE derived from pancreatic cancer patients showed antitumoural activity in vitro [ 7 ]. Furthermore, it has recently been reported that FcεRI expression [ 8 ] and greater numbers of eosinophils and basophils, key IgE receptor (FcεR)-expressing effector cells [ 9 , 10 , 11 ], may be associated with improved outcomes for cancer patients. In mice, where it should be noted the human IgE system is not fully recapitulated and expression of the high-affinity IgE receptor (FcεRI) is only present in mast cells and basophils, a carcinogen-induced IgE response was protective against carcinogenesis [ 12 ], but conversely an inflammation-driven polyclonal IgE response promoted tumour outgrowth [ 13 ].…”
Section: Introductionmentioning
confidence: 99%